Efektivitas Pupuk Organik Feses Kuda Hasil Pembakaran Terhadap Pertumbuhan Tanaman Cabai Merah Keriting (Capsicum annum L.) - Darmawan Risal; Nurul Mukhlishah (Jurnal Ecosolum, 2019)
Organic material derived from horse manure is very abundant and has the potential to be used as organic fertilizer with good nutrient content for plants. This study to utilize organic manure from combustion for growth and productivity of the red chili. In addition, this research was conducted to obtain the right composition of fertilizer doses to increase the growth and production of curly red chili. The method to use the Alfisol soil growing media at the site using polybag by treating different doses on each treatment. The number of treatments were given doses of 0 g (P0), 1 g (P1), 284 g (P2), 426 g (P3) and 568 g (P4) with replications each three times. Analysis metode for use macro nutrient content (N, P, K) and data collection in the form of plant height, leaves, production and environmental factors. Data analysis used Duncan α 0.05. The results of the analysis of the treatment effect on plant height were P4 (Media of soil with combustion horse fertilizer from 568 g) treatment significantly different from other treatments. While other treatments did not show a significant difference in plant height. The effect of treatment on the number of leaves showed no real effect. In the growth and production of curly red chilies there are markedly significant differences. P4 is significantly different from P3, P2, P1 and P0. Whereas P3 is not significantly different from P1 as well as P2 which is significantly different from other treatments. P4 is a treatment with a large number of fruits with an average of 10.3 pieces. While treatment with a small number of fruits is P0 with an average of 2.3 fruits. Combustion horse manure organic fertilizer is quite effective in increasing the growth and production of red chili. It can be assessed from the development of plant height and number of fruits on curly red chili plants. The dose of horse manure organic fertilizer which is good enough for curly red chili plants is 568 g.